The Response of Some Yardlong Bean (Vigna unguiculata subsp. Sesquipedalis) Accessions to Bradyrhizobium Inoculation - Mita Kathalia; Taryono Taryono; Rahmi Sri Sayekti (Agrotechnology Innovation (Agrinova), 2020)
Yardlong bean (Vigna Unguiculata subsp. Sesquipedalis) is very potential commodity to be developed in Indonesia and Rhizobium has played an important role to increase pod production through free nitrogen ixation. Bradyrhizobium is a species of Rhizobium that is commonly found in vigna. The purpose of this study was to determine the response of twenty accessions of yardlong beans to Bradyrhizobiuminoculation and determine effective accessions with Bradyrhizobium inoculation. This research was conducted at AIC-UGM from March to July 2019. The planting material was 20 accessions of yardlong beans from AIC-UGM collection using seed inoculation methods. The result after inoculation of Bradyrhizobium treatment showed that the innoculation enhances plant height, number of leaves, root volume, root area, root length, root fresh weight, root dry weight, pod fresh weight, number of pods, number of effective root nodules, amount of root nodules and accelerate the age of lowering and harvest age in most accessions. Considering its response to the Bradyrhizobium inoculation, accessions of yardlong bean that have the potential to be developed for superior varieties are FBKP 143, FBKP 146, FBKP 147, FBKP 150, FBKP 152, FBKP 161 and FBKP 162.